Estabilidade de pontos de equilíbrio e existência de soluções periódicas em alguns modelos bidimensionais - Oliveira, Salvador Tavares de [UNESP] (2015)
This work presents stability criteria for equilibrium points of nonlinear systems of ordinary di erential equations, in particular the Lyapunov methods (direct and indirect). We also look at some criteria that enable us sometimes determine the existence of periodic solutions. In particular, a variation of the classic predator-prey model is analyzed for the existence of periodic solution